Characterization and Evaluation of Iron Oxide Nanoparticles Prepared Using Hydrogel Template Based on Phosphonate Alginate - Tamer, T.M.; Abou-Taleb, W.M.; Roston, G.D.; Mohyeldin, M.S.; Omer, A.M.; Shehata, E.F. (Nanoscience & Nanotechnology-Asia, 2019)
Background: Currently, the use of nano-sorbent for the aqueous heavy metals removal is popular among researchers. Methods: In this study, iron oxide nanoparticles were developed as a promising adsorbent for Cr (VI) removal from its aqueous solution. Simple template surface method based on phosphonated alginate biopolymer was employed for the nanoparticles preparation. Different physical characterization tools such as FT-IR, SEM, TEM, XRD and magnetic properties were applied to investigate the physicochemical character of the developed nanoparticles. Batch experiments were used to study the applicability of iron oxide nanoparticles for Cr (VI) removal from aqueous solutions under different preparation conditions. The effects of initial Cr (VI) concentration, pH, adsorbent dosage, contact time and temperature on the removal process were also optimized. Results indicate that the removal efficiency of Cr (VI) increased from 14.44% to 67.85% with increasing iron oxide nanoparticles dosage from 0.025g to 0.3g. Furthermore, the removal percent rose from 39.11% to 56.04% by increasing the environmental temperature up to 50°C. While it decreased with increasing initial concentration of Cr (VI). Results: The best results of removal were recorded at pH=2. Conclusion: Overall, the obtained results indicate that the developed iron oxide nanoparticles could be effectively used as adsorbents for removal of Cr (VI) from aqueous solutions.
Keywords: biopolymer